Working Conditions and the Components of Burnout Among Nursing Staff in a Public Hospital in Mexico City. Issue 4 (28th August 2022) - MOLINA ZAVALA, Brenda I.; ZAMORA-MACORRA, Mireya; MARTÍNEZ ALCÁNTARA, Susana
ABSTRACT: Background: Working conditions in public hospitals in Mexico City are highly demanding. The need for healthcare is pressing, materials and instruments are scarce, and exposure to pain and suffering is constant. These adverse conditions have an adverse impact on the physical and mental health of healthcare professionals. The nursing staffs are among those who are most affected, and they frequently experience burnout syndrome or one of its several dimensions, including emotional exhaustion, depersonalization, and reduced personal accomplishment. Purpose: The aim of this research was to analyze the relationship among working conditions, related stress, and the dimensions of burnout syndrome in a tertiary care public hospital in Mexico City. Methods: A cross-sectional design was applied on a random sample of 190 nurses in a public hospital in Mexico City. Working conditions and burnout syndrome were evaluated using standardized instruments. Adjusted prevalence ratios were calculated. Three clusters, one for each burnout dimension, were generated and then evaluated using a correspondence analysis with labor characteristics. Results: One quarter (25%) of the participants self-reported a sense of personal accomplishment, and 12% reported emotional exhaustion and depersonalization. The labor variables that were found to be associated with the dimensions of burnout were workload, performing potentially hazardous work, and conducting tedious tasks. Positive conditions were shown to decrease the prevalence of burnout in all three dimensions. Conclusions/Implications for Practice: Working conditions for nursing staff impact the mental health of nurses and affect the quality of the healthcare they provide. The set of work demands and stressors to which they are exposed should be controlled and modified to ensure a healthy work environment.